การเพิ่มประสิทธิภาพของการอบแห้งในโรงงานผลิตยางแท่ง STR20 - พรศิริ แก้วประดิษฐ์ (มหาวิทยาลัยสงขลานครินทร์, 2021)
This research has focused on drying optimization for blocked rubber STR20 industry to guarantee dried product qualities. Initially, a set of polynomial equations (degree 2 and 3), which is the correlation of inputs (drying time and temperature) and outputs (moisture content, initial plasticity and plasticity retention index), has been developed with and without relative changes in both the inputs and the outputs based the experimental data sets (114 data). The optimum coefficients have been determined via MATLAB program (fminsearch function) by minimizing sum square difference between the predicted and experimental output. The simulation results show that polynomial of degree 3 with input interactionterms gives lowest prediction error, SSE = 1.468 and MSE = 0.489. The prediction equations have further been used for optimization purpose; two types of optimization problems have been investigated such as constant and step-change of the desired operating variables. For the second optimum problem, since of the dynamic optimization requirement the change rate equations of the product qualities have been proposed in this research based the predicted data set to overcome the limitation of the